2017
DOI: 10.1002/em.22071
|View full text |Cite
|
Sign up to set email alerts
|

Developmental programming: Interaction between prenatal BPA and postnatal overfeeding on cardiac tissue gene expression in female sheep

Abstract: Epidemiologic studies and studies in rodents point to potential risks from developmental exposure to BPA on cardiometabolic diseases. Furthermore, it is becoming increasingly evident that the manifestation and severity of adverse outcomes is the result of interaction between developmental insults and the prevailing environment. Consistent with this premise, recent studies in sheep found prenatal BPA treatment prevented the adverse effects of postnatal obesity in inducing hypertension. The gene networks underly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 93 publications
(123 reference statements)
0
11
0
Order By: Relevance
“…As opposed to lack of effect of prenatal BPA on fetal male liver, prenatal BPA treatment increased the heart/body weight ratio at GD90 in males, alone. Consistent with the lack of effect on the female heart during fetal life, there were no effects of prenatal BPA treatment on blood pressure or morphometric measures in adult BPA‐treated offspring (Koneva et al, ; MohanKumar et al, ). However, prenatal BPA treatment upregulated several genes involved in the regulation of myocardium growth, heart development and remodeling, and the downregulation of genes involved in cellular respiration and inflammation in adult prenatal BPA‐treated females (Koneva et al, ).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…As opposed to lack of effect of prenatal BPA on fetal male liver, prenatal BPA treatment increased the heart/body weight ratio at GD90 in males, alone. Consistent with the lack of effect on the female heart during fetal life, there were no effects of prenatal BPA treatment on blood pressure or morphometric measures in adult BPA‐treated offspring (Koneva et al, ; MohanKumar et al, ). However, prenatal BPA treatment upregulated several genes involved in the regulation of myocardium growth, heart development and remodeling, and the downregulation of genes involved in cellular respiration and inflammation in adult prenatal BPA‐treated females (Koneva et al, ).…”
Section: Discussionmentioning
confidence: 77%
“…Consistent with the lack of effect on the female heart during fetal life, there were no effects of prenatal BPA treatment on blood pressure or morphometric measures in adult BPA‐treated offspring (Koneva et al, ; MohanKumar et al, ). However, prenatal BPA treatment upregulated several genes involved in the regulation of myocardium growth, heart development and remodeling, and the downregulation of genes involved in cellular respiration and inflammation in adult prenatal BPA‐treated females (Koneva et al, ). Prenatal BPA treatment was also found to reduce collagen expression in the right ventricle (MohanKumar et al, ).…”
Section: Discussionmentioning
confidence: 77%
“…Importantly, previous studies have demonstrated that the postnatal environment could amplify the final phenotypic outcomes programmed by early developmental insults [27][28][29]. Nonetheless, to the best of our knowledge, no studies have reported on the responsiveness of intestinal function to postnatal insults, ensuing the metabolic disruptions programmed by prenatal BPA exposure.…”
Section: Introductionmentioning
confidence: 93%
“…Maternal hyperglycemia in pregnancy is independently associated with the offspring’s risk for glucose intolerance, obesity and an increase in blood pressure in seven-year-old children, with only girls being obese [ 51 ]. In female sheep, after prenatal bisphenol A (BPA, commonly found in polycarbonate plastic and epoxy resins) exposure, postnatal overfeeding/adiposity, and the combination, led to myocardial transcriptional changes, and despite different gene profiles, still influenced similar signaling pathways [ 21 ]. Genes altered by the programming insult were implicated in obesity, hypertension or heart disease [ 21 ].…”
Section: High Fat Programming: Sex-specificity Altered Cardiac Gementioning
confidence: 99%
“…In female sheep, after prenatal bisphenol A (BPA, commonly found in polycarbonate plastic and epoxy resins) exposure, postnatal overfeeding/adiposity, and the combination, led to myocardial transcriptional changes, and despite different gene profiles, still influenced similar signaling pathways [ 21 ]. Genes altered by the programming insult were implicated in obesity, hypertension or heart disease [ 21 ]. In rats, a maternal HFD causes cardiac hypertrophy; increases cardiac susceptibility to ischemic-reperfusion injury only in adult male offspring, and differentially regulates cardiac angiotensin II (AngII) receptor type 1 (AGTR1) and type 2 (AGTR2) expression [ 48 ].…”
Section: High Fat Programming: Sex-specificity Altered Cardiac Gementioning
confidence: 99%